An SPL reference model based on domain taxonomies & standards - Buccella, Agustina (2022)
Building reusable software is always a challenge, even when well-established approaches are applied. Software Product Line (SPL) development is one these approaches, which allows domain modeling be a way of dealing with common and variable aspects of reality. However, domain engineering itself can be complex, many times depending on the domain scope and/or its associated functionality. In this paper, our proposal to SPL development is structured as a leveled reference model built upon standardized semantic resources. This model and its associated process are exemplified through several cases from the field, drawing influ- encing factors subjectively assessed. Our experiences show that systematically enriching domain engineering may improve SPL development in the practice.